PORNOGRAPHIC CYBERWORLD - REFLECTIONS ON ARTICLE 202 OF THE PENAL CODE - Basior, Ewa (Człowiek w cyberprzestrzeni, 2020)
Pornography as a social phenomenon has never been unequivocally defined due to the multiplicity of forms and possible means of communication. Each content is assessed individually in isolation from other cases. The mentioned phenomenon can not only be characterized by sexuality, sexuality, nudity or obscenity, especially when it is so multidimensional and multifaceted. Pornography has long entered a new dimension, into a space where it can be improved and also gain efficiency. It's her cyberspace. The virtual world is full of lascivious temptations. Animated sexual positions undoubtedly constitute pornographic content as in the case of a movie or an animated figure of this nature. It can be chosen because of the adaptation of erotic fantasies, but it can also be a model for dealing with the victim in reality. The performers are looking for newer and stronger stimuli in the form of more extreme pornographic materials